FAKTOR-FAKTOR YANG MEMENGARUHI EKSPOR DAN PROSPEK EKSPOR PISANG PROVINSI LAMPUNG - Sirilus Gatya Prasasta; Raden Hanung Ismono; Suriaty Situmorang (Lampung University, 2022)
This study aims to determine the factors that influence the exports volume of Lampung Province’s bananas and predict the exports of Lampung Province’s bananas. This research based on the exports of some kind of banana produced by firm and by the corporation program involving the firm and smallholder farmers. This study used both descriptive and quantitative analysis methods and data werw obtained from the relevant authorities as secondary data for 5 years, starting from the first quarter of 2015 to the first quarter of 2020. The data were analyzed by regress time series data using Ordinary Least Square Method (OLS) and Autoregressive Integreted Moving Average (ARIMA). The results of this study showed that the factors that significantly affect the exports volume of Lampung Province’s bananas are domestic banana production and the average of domestic banana price index. The trend of banana exports prospect until the end of 2024 decreases. Key words: banana, exports prospect, Lampung, factor